تطبيق وسائل التعليم لوحة النشرات "Bulletin Board " لتدريس مهارة القراءة - Mudlofir, Ali; Baihaqi, Muhammad; Anisyah, Suci Nur; L, Achmad Misbachul; Tamara, Aisyi (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
The ability of students will increasingly decline if the cause is not known. One of the impacts is that students’ potential is left behind when learning Arabic. This is what makes it the task of educators to understand what methods should be used for teaching and learning activities. This study aims to help them get to know Arabic for students, and to develop the process of teaching Arabic by using the Bulletin Board media on maharoh qiro’ah. The target sample is class X Mtsn Jabal Nur Sidoarjo through a qualitative approach method. The results of this study are the use of media to facilitate the process of class X students of Mtsn Jabal Nur Sidoarjo learning Arabic for students and developing the process of teaching Arabic by using bulletinboards and developing and adding to the treasures of knowledge in the field of language. The use of bulletinboard media is a used to show examples of student work, charts, pictures, posters and objects in 3D. With this media, it is hoped that it can increase the innovation and creativity of educators in helping the teaching and learning process to be more interesting and easy to understand for students at Mtsn Jabal Nur Sidoarjo.